Pengaruh Penambahan Pasta Kunyit (Curcuma Longa L) Terhadap Total Bakteri Dan Sifat Organoleptik Daging Ayam Broiler Segar - Nurlaela Hermawan, Desti; Falahudin, Aaf; Imanudin, Oki (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2024)
This study aims to determine the effect of the level of adding turmeric paste (Curcuma longa L.) on the number of bacteria and pH value of chicken meat, as well as organoleptic characteristics including color, odor and texture consistency. The research method was carried out experimentally using a Completely Randomized Design (CRD) with four turmeric paste concentration treatments: P0 (control), P1 (10 ml), P2 (20 ml), and P3 (30 ml) and repeated five times. The results showed that the addition of turmeric at concentrations of 10 ml, 20 ml and 30 ml significantly reduced the number of bacteria compared to the control (P<0.05) with the highest number of bacteria at P0 of 6.14 x 10⁶ cfu/ml and the number of bacteria the lowest at P3 was 3.20 x 10⁶ cfu/ml, the number of bacteria in all treatments still did not meet the Indonesian National Standard (SNI 7388:2009 10⁶ cfu/g). The pH value in each treatment with the addition of turmeric paste was not significantly different (P > 0.05), with a pH range of 5.39 (P0) to pH 5.60 (P3). The addition of turmeric paste improves the organoleptic quality of meat, especially in terms of yellower color, better aroma, softer texture. In conclusion, turmeric paste can reduce the number of bacteria and improve the characteristics of chicken meat.